Synergistic effect of microRNA and albumin-bound nanoparticles for inhibition of glioblastoma cancer cell proliferation (Brazilian Journal of Pharmaceutical Sciences, 2020)
The functional significance of upregulation miR-34a in combination with albumin-bound paclitaxel nanoparticles in U251 glioblastoma cell line has been evaluated. The MTT assay determined that miR34a and albumin-bound paclitaxel nanoparticles can reduce cell viability, but the combination of both factors has a stronger effect on cell viability. The application of qRT-PCR has demonstrated that the transduction of miR-34a could lead to exogenous upregulation of miR-34a level and downregulation of SURVIVIN. Moreover, treatment of U251 cells with miR-34a and nanoparticles together considerably inhibit SURVIVIN expression compared to miR-34a and nanoparticles alone. Flow cytometry showed that upon miR-34a overexpression cell cycle arrested in G1 phase, while treatment with nanoparticles increased the cell population in G2 phase. Upregulation of miR-34a along with treatment with nanoparticles elevated the number of cells arrested in G1/ G2 phases of the cell cycle. Expression of miR-34a with albumin-bound paclitaxel nanoparticles reduced cell viability, downregulated SURVIVIN and enhanced cell cycle arrest in G1/G2 phases. Thus, the upregulation of miR-34a with these nanoparticles are potential candidates therapeutic for glioblastoma cancer.